2021
DOI: 10.3390/polym13172849
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Adhesion and Mechanical Properties of Wood-Polymer Hybrid Composites Prepared by Injection Molding

Abstract: Birch (Betula pendula Roth.) and beech (Fagus sylvatica L.) solid wood and plywood were overmolded with polyamide 6 (PA 6) and polypropylene (PP) to investigate their mechanical properties and interfacial adhesion. In the case of PA 6, maximum tensile shear strengths values of more than 8 to 9 MPa were obtained for birch and beech, respectively. The values are comparable to bond strengths of commercial joints bonded with formaldehyde-containing amino-plastics. Perpendicular to the wood elements, bond strength … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 43 publications
0
8
0
Order By: Relevance
“…To test the welding shear strength, a gap is cut 39 mm away from the two ends, and a connection interface of 2 mm  4 mm can be obtained, 37,38 and then the welding shear strength is tested by the universal material testing machine. For the purpose of observing the distribution status of CFs at the interface, a 20-μm-thick slice was cut from the sample interface in the vertical direction.…”
Section: Welding Principle and Experimental Apparatusmentioning
confidence: 99%
“…To test the welding shear strength, a gap is cut 39 mm away from the two ends, and a connection interface of 2 mm  4 mm can be obtained, 37,38 and then the welding shear strength is tested by the universal material testing machine. For the purpose of observing the distribution status of CFs at the interface, a 20-μm-thick slice was cut from the sample interface in the vertical direction.…”
Section: Welding Principle and Experimental Apparatusmentioning
confidence: 99%
“…The creep behaviors of WPCs arise from their viscoelastic nature [ 27 ] and are influenced by factors such as the composition, compatibility, and nature of the components, as well as moisture. Reduced interfacial adhesion between wood and the polymer matrix results in creep behavior and diminished performance [ 28 ]. This incompatibility can be mitigated by using functional polyolefin as a coupling agent, enabling improved stress transfer between the polymer matrix and wood filler [ 29 , 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Polyethylene (PE) is the most commonly used polymer matrix in WPC production routes [ 43 , 44 , 45 , 46 ]. Also, other thermoplastic polymers are widely used: polypropylene (PP), polystyrene (PS), poly (vinyl chloride) (PVC), and acrylonitrile butadiene styrene (ABS) [ 24 , 28 , 35 ]. High-density polyethylene (HDPE) is considered highly crystalline among PEs [ 36 ], with a melting temperature of around 130 °C, making it suitable for processing with wood [ 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…Nylon (PA) and polypropylene (PP) have good mechanical performance and wear resistance, and are easily formed by injection molding. Stadlmann et al 18 prepared wood-polymers (PA, PP) by overmolding and concluded that PA6 has optimal tensile shear strength.…”
Section: Introductionmentioning
confidence: 99%